Biologia Comparada De Populações Da Lagarta–Do–Cartucho Em Folhas De Milho E Mandioca - Machado, Keneson Klay Gonçalves; De Lemos, Raimunda Nonata Santos; Medeiros, Fabíola Rodrigues [UNESP] (My University, 2014)
The fall armyworm is a pest that feeds on various botanies species. The objective of this experi-ment was to study the biology of this pest in corn and cassava leaves. Caterpillars were collected in area under cultivation with cassava and maintained on artificial diet for two generations. Under controlled conditions in a climatic chamber (B.O.D) in the laboratory (25 ºC, 60 ± 10% RH and photophase 14 hours) were evaluated daily 50 caterpillars in corn treatments and 50 in cassava, where duration and viability of the larval phase and pupal, weight of pupas were observed after 24 hours, deformation percentage of pupas and adults, longevity, fecundity and total life cycle. The viability of larvae fed on leaves of maize and cassava was 74% and 60%, respectively. The larval period of the insects was shorter in maize 16.89 days (seven instars) and cassava 20.08 days (six instars). The pupal phase lasted 11.42 days in cassava treatment and 10.87 in the maize. The pupal weight of females and males was higher in corn 204.91 mg and 198.97 mg, respectively. The biological cycle varied depending on the ingested food. Adult longevity lasted 9.88 days for insects fed on cassava leaves. Therefore, cassava affected the development of S. frugiperda.
Comparative biology of fall armyworm populations in corn and cassava leaves
Keywords: Biology; Manihot esculenta; Spodoptera frugiperda; Zea mays